Herbal Drug Interactions - Samee Mukadam, Masarrat; Mohammad Amaan Mohammad Rafique, Shaikh; Jamir Tamboli, Swaleha; Hifzan Ulde, Nawal (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Herbs have been used since ages for the treatment of various diseases. As herbs are obtained from plants and are a naturally occurring source, people considered it safe. They are not aware about the interaction of herbal medications that will lead to several side effects. The administration of herbal medicines in combination with therapeutic drugs causes the interaction between phytochemicals present in herbal medicines and active ingredients in prescribed drugs that leads to herb-drug interactions. The interactions may be pharmacodynamics and pharmacokinetics. Nowadays people self-administer herbal medicines. It is observed that many individuals who use herbal medicines do not report that to their physician and pharmacist. This review focuses on the interaction of herbal medicine and risk associated when herbs such as Ginkgo (Ginkgo biloba), Garlic (Allium sativum), Kava (Piper methysticum), Echinacea (Echinacea purpurea), Danshen (Salvia miltiorrhiza), St.John’s wort (Hypericum perforatum) use in combination with therapeutic agents. To make people, physicians and pharmacists aware about herb-drug interactions, pharmacological actions and side effects associated with it.